Implementasi Tema Arsitektur Minimalis Terhadap Ruang Kerja pada Perencanaan dan Perancangan Consultant Co-Working Space di Kota Denpasar: Bahasa Indonesia - Dian Tri Krismianti; I Gede Surya Darmawan; I Nyoman Nuri Arthana (Program Studi Arsitektur, Fakultas Teknik Universitas Warmadewa, 2023)
Changes in the culture of the global community in the world of work continue to experience changes along with the development of technology. Workers who initially had to come to the office to work are now able to work anywhere more flexibly, not a few also choose to start a business to develop their careers. In this digital era, everything requires digitization to develop their business, one of the right ways is to hire professional consulting services to help these business actors develop their business. Therefore, planning and designing a co-working space consultant was made to accommodate the consultant workers and their clients in their needs to work. The image of a consultant that looks professional, neat, authoritative and clean makes the minimalist architectural theme suitable for describing their work. The purpose of applying the minimalist architectural theme to this consultant's work space is to create a professional working atmosphere and produce more optimal performance. This study uses a qualitative-descriptive method to analyze theory and data collection. The results of the research are in the form of a minimalist architecture implementation design for consultant workspaces at the Planning and Design Consultant Co-Working Space in Denpasar City.